Computational information geometry : for image and signal processing - Nielsen, Frank; Critchley, Frank; Dodson, C. T. J. (Springer, 2017)
This book focuses on the application and development of information geometric methods in the analysis, classification and retrieval of images and signals. It provides introductory chapters to help those new to information geometry and applies the theory to several applications. This area has developed rapidly over recent years, propelled by the major theoretical developments in information geometry, efficient data and image acquisition and the desire to process and interpret large databases of digital information. The book addresses both the transfer of methodology to practitioners involved in database analysis and in its efficient computational implementation.
Keywords: Signal processing -- Digital techniques -- Mathematics.; Image processing -- Digital techniques -- Mathematics.; elektronické knihy; electronic books